2020
DOI: 10.1080/21645515.2020.1785791
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic signature of invasive non-typhoidal Salmonella in Africa: implications for vaccine development

Abstract: Invasive non-typhoidal Salmonella (iNTS) infections are a leading cause of bacteremia in Sub-Saharan Africa (sSA), thereby representing a major public health threat. Salmonella Typhimurium clade ST313 and Salmonella Enteriditis lineages associated with Western and Central/Eastern Africa are among the iNTS serovars which are of the greatest concern due to their case-fatality rate, especially in children and in the immunocompromised population. Identification of pathogen-associated features and host susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 183 publications
(428 reference statements)
0
21
0
Order By: Relevance
“…In addition to AMR, the ST313 lineages have accumulated loss-of-function mutations (genome degradation) 12 . Evidence of host adaptation in ST313 involved specific pseudogenes that inactivated gene function and modified metabolic and virulence phenotypes 5 , 13 – 18 .…”
Section: Mainmentioning
confidence: 99%
“…In addition to AMR, the ST313 lineages have accumulated loss-of-function mutations (genome degradation) 12 . Evidence of host adaptation in ST313 involved specific pseudogenes that inactivated gene function and modified metabolic and virulence phenotypes 5 , 13 – 18 .…”
Section: Mainmentioning
confidence: 99%
“…The early immune response against Salmonella relies on innate immunity within the gut mucosa. In general, antibodies are necessary for resistance to systemic Salmonella infections, and as the infection progresses, an effective immune response to Salmonella relies on humoral immunity, which can provide effective protection to the host ( 20 , 21 ). A previous study reported that a novel live S .…”
Section: Discussionmentioning
confidence: 99%
“…This yielded a similar culture positivity-rate to other sample-types, and yielded a much wider range of STs/serovars. The fact that Salmonellae have a more diverse ecology in the household environment than previously appreciated in this setting contrasts with the narrow range of STs that cause human invasive disease [43]. The lack of overlap between the ecological niches of serovars causing colonising the household and causing human bloodstream categories is very striking.…”
Section: Discussionmentioning
confidence: 99%